Pompey Pop. (24th January 2020) - Allen, Dave
Abstract : This article provides a retrospective account of the author's long-time involvement with 'PompeyPop', a project uncovering the somewhat neglected history of the impact of popular music inPortsmouth. The article demonstrates how the dedication of the author, a retired employeeof Portsmouth University, to this community initiative has established the importance of popularmusic to this working-class city and, most importantly, how it has challenged notionsof 'mainstream' history. After describing the growth of light entertainment in post-SecondWorld War Portsmouth, it challenges a number of preconceptions, ranging from notions ofnew styles 'sweeping away' their predecessors, to tokenized histories of the post-war periodalways being 'depressed', to notions of the swinging sixties being centred exclusively in certainparts of London. Regarding the latter, the article outlines a methodological problem, wherewriters such as Dominic Sandbrook are regarded as focusing exclusively on archival research, asopposed to also including the oral histories of ordinary people who lived through the period.